Aromatase Inhibitors Plus Weight Loss Improves the Hormonal Profile of Obese Hypogonadal Men Without Causing Major Side Effects - Colleluori, Georgia; Chen, Rui; Turin, Christie G.; Vigevano, Francesca; Qualls, Clifford; Johnson, Biju; Mediwala, Sanjay; Villareal, Dennis T.; Armamento-Villareal, Reina (Frontiers in Endocrinology, 2020)
OBJECTIVE: In obese men, the increased expression of the aromatase enzyme in adipose tissue leads to high conversion of androgens to estrogens contributing to hypogonadotropic hypogonadism (HHG). Our objective is to evaluate efficacy and safety of weight loss (WL) plus aromatase inhibitor (AI) therapy in severely obese men with HHG. We hypothesize that AI+WL will be more effective as compared to WL alone in improving the hormonal profile, thus muscle strength and symptoms of HHG (primary outcomes), with no significant adverse effects on lean mass, metabolic profile and bone mineral density (secondary outcomes). DESIGN: Randomized double-blind placebo-controlled pilot trial. METHODS: Twenty-three obese men (BMI≥35kg/m2), 35-65 years old, were randomized to weight loss (diet and exercise) plus either anastrozole (AI+WL, n=12) at 1 mg daily or placebo (PBO+WL, n=11) for 6 months. Inclusion criteria: total testosterone<300 ng/mL (average of 2 measurements), estradiol≥10.9 pg/ml, LH<9 IU/l. Symptoms of hypogonadism by questionnaires; muscle strength by Biodex dynamometer; body composition and bone mineral density by dual-energy X-ray absorptiometry; bone microarchitecture and finite element analysis by high resolution peripheral quantitative-computed tomography. RESULTS: After 6 months of therapy, AI+WL group had higher testosterone (p=0.003) and lower estradiol (p=0.001) compared to PBO+WL. Changes in symptoms and muscle strength did not differ between groups. AI+WL resulted in higher fat mass loss than PBO+WL (p=0.04) without differences in changes in lean mass. Total and LDL cholesterol reduced more in the PBO+WL group compared to AI+WL (p=0.03 for both), who experienced a minimal increase with unlikely meaningful clinical impact. Tibial trabecular bone area decreased more in PBO+WL than AI+WL group for which it remained stable (p=0.03). CONCLUSIONS: Although AI+WL is effective in reversing the hormonal profile of HHG in severely obese men without causing major side effects, it does not lead to greater improvements in muscle strength and symptoms of hypogonadism compared to WL alone.